Additive Manufacturing and Augmented Reality as New Production Technologies in the Aviation Industry - M. G. Yevtodyeva (Vestnik MGIMO-Universiteta)
Abstract: The image of the global aviation industry is dramatically changing. This derives in the first instance from dynamic development of the military and civil aircraft market, where a significant growth in demand and an increase in airliner deliveries over the next 15 years by at least 80% was forecasted. Aircraft manufacturers' revenues in services business, including maintenance, repair and overhaul (MRO) are boosting, too. All this provide favorable conditions for the development of new production technologies in the aviation sector, including Additive Manufacturing (AM) and Augmented Reality (AR). Though the research and development in the field of AM an AR began in the 1980s, only in the last decade AM and AR technologies have reached the necessary level of maturity to be widely used in design, manufacturing and assembly processes in aeronautics, including civil and military aircraft. There are good prospects for their use in aircraft’ maintenance, repair and overhaul as well.  The transition from the initial period of formation of AM and AR technologies to the stage of technological growth and rapid development of relevant markets is evidenced by a number of factors. First of all, they include establishment of "dominant" technological designs based on AM and AR (certified additive production methods, new materials based on AM and machines for their production, special Augmented Reality headsets, etc.), as well as beginning of serial production of many AM-components and AR-platforms for the aviation industry. The participation of major aircraft manufacturers such as Boeing and Airbus in AM and AR R&D projects, the formation of "new" supply chains, the development of public-private partnerships (e.g. NAMII in the U.S.), as well as the formation of consortia and alliances of companies that develop and produce systems and parts for aircraft based on additive technologies and augmented reality, are also indicators of the transition to a new stage of development of these technologies and markets.